Bacterial community structure is indicative of chemical inputs in the Upper Mississippi River - Staley, Christopher; Gould, Trevor J.; Wang, Ping; Phillips, Jane; Cotner, James B.; Sadowsky, Michael J. (Frontiers in Microbiology, 2014)
Local and regional associations between bacterial communities and nutrient and chemical concentrations were assessed in the Upper Mississippi River in Minnesota to determine if community structure was associated with discrete types of chemical inputs associated with different land cover. Bacterial communities were characterized by Illumina sequencing of the V6 region of 16S rDNA and compared to >40 chemical and nutrient concentrations. Local bacterial community structure was shaped primarily by associations among bacterial orders. However, order abundances were correlated regionally with nutrient and chemical concentrations, and were also related to major land coverage types. Total organic carbon and total dissolved solids were among the primary abiotic factors associated with local community composition and co-varied with land cover. Escherichia coli concentration was poorly related to community composition or nutrient concentrations. Abundances of 14 bacterial orders were related to land coverage type, and seven showed significant differences in abundance (P ≤ 0.046) between forested or anthropogenically-impacted sites. This study identifies specific bacterial orders that were associated with chemicals and nutrients derived from specific land cover types and may be useful in assessing water quality. Results of this study reveal the need to investigate community dynamics at both the local and regional scales and to identify shifts in taxonomic community structure that may be useful in determining sources of pollution in the Upper Mississippi River.